Електронне врядування як чинник активізації політичної участі в Україні - Ямельницький, Олег (Видавництво Львівської політехніки, 2012)
It’s considered good governance and e-government as factor of activation of political participation in Ukraine. An attention is paid to the main features of good governance, such as participatory, consensus oriented, responsiveness, equity and inclusiveness, accountability, transparency, effectiveness and efficiency, rule of law. The process of e-government treats as the improving factor of political participation in Ukraine.
Keywords: "добре"; "належне" врядування; активізація політичної участі; електронне врядування